2015
DOI: 10.18052/www.scipress.com/ilns.38.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intra-Row Spacing of Sesame (<i>Sesamum indicum</i> L.) and Frequency of Weeding on Yields of Maize-Sesame Intercrop in Makurdi, Nigeria

Abstract: ABSTRACT. Field experiments were conducted from July to October, during 2012 and2013 cropping seasons, at the Research Farm, University of Agriculture, Makurdi, Nigeria, to evaluate the effects of intra-row spacing of sesame and frequency of weeding on yields of maize-sesame intercrop. The trial was a 3 x 3 factorial experiment fitted in a randomized complete block design with four replications. Nine of the treatments consisted of intercropped maize with sesame sown at the intra-row spacing of 10 cm, 15 cm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…This was in agreement with the findings of Donkor et al, (2018), who indicated that row-planting increases efficiency by reducing overcrowding decreases competition for nutrients and water intake. It was J o u r n a l P r e -p r o o f also in agreement to the study by Ijoyah et al, (2015), who preferred row planting method over broadcast for improved production.…”
Section: Demographic and Socioeconomic Background Of Sampled Householdssupporting
confidence: 85%
“…This was in agreement with the findings of Donkor et al, (2018), who indicated that row-planting increases efficiency by reducing overcrowding decreases competition for nutrients and water intake. It was J o u r n a l P r e -p r o o f also in agreement to the study by Ijoyah et al, (2015), who preferred row planting method over broadcast for improved production.…”
Section: Demographic and Socioeconomic Background Of Sampled Householdssupporting
confidence: 85%
“…This view supperts that of Silwana and Lucas (2002) who reported that intercropping reduced grain and stover yeild of component crops. Present findings are in acordence with the findings of Ijoyah et al (2015) reported that this was associated with the highest total intercrop yields and lowest competative ratio.…”
Section: (B) Studies On Crop Yield In Intercropping Systemsupporting
confidence: 92%
“…The biggest spacing between the rows lead to the lesser competition between plants for available nutrients and other growth resources (Olowe and Busari, 1994;Ngala et al, 2013). These results are in agreement with the Caliskan et al (2004), Ijoyah et al (2015), Ngala et al (2013) in sesame and Dugje and Odo (2006) in the millet.…”
Section: Plant Height (Cm)supporting
confidence: 91%